Faktor-Faktor yang Memengaruhi Cash Holding Perusahaan - Audrey Dwi Mas Rustam; Rosmita Rasyid (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
This study was conducted to examine the effect of profitability, leverage, liquidity, cash flow, and sales growth toward cash holding on the miscellaneous industrial sectors and consumer goods industry firms listed on the Indonesia Stock Exchange (IDX) in 2017-2019. The sample used in this study is 102 samples. The sampling method used in this study is purposive sampling with predetermined criteria. The hypothesis testing is done by multiple regression analysis. This study used EViews 12 for processing the data. The results of this study indicate that profitability has a significant positive effect on cash holding, meanwhile other variable which are leverage, liquidity, cash flow, and sales growth have no significant effect on cash holding.